(untitled) (European Journal of Economics, Finance and Business Development, 2026)
This article empirically examines the impact of digital transformation on Uzbekistan’s investment attractiveness using correlation-regression analysis methods. Based on official data from UNCTAD, the World Bank, and IT Park for the period 2018–2023, a very strong relationship was established between the number of IT Park residents and IT services exports (r = 0.994, p < 0.001), and between fintech companies and online payments (r = 0.998, p < 0.001). However, the relationship between FDI and internet coverage was found to be statistically insignificant (p > 0.05), indicating that investment decisions depend not only on infrastructure but more so on the quality of the institutional environment. Regional comparison (Uzbekistan, Kazakhstan, Georgia) reveals that Uzbekistan leads the region in IT export growth (+1,114%, 2018–2023), yet lags behind neighboring countries in the FDI/GDP ratio (2.4%) and institutional indicators.